Q: What is 3x cubed squared and the 3x cubed is in parenthesis?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x2y2)3 + (x3y3)2 = 2x6y6.

(3x)3 = 27x3 (We think the original form was simpler.)

if you take your time youll figure out its e=mc2

The 3x is cubed and the 4x is squared

This is impossible as the variables are different

Related questions

x cubed y cubed z squared

(x2y2)3 + (x3y3)2 = 2x6y6.

(3x)3 = 27x3 (We think the original form was simpler.)

if you take your time youll figure out its e=mc2

(x + 2)(3x - 1)(3x + 1)

The 3x is cubed and the 4x is squared

the derivative of 3x is 3 the derivative of x cubed is 3 times x squared

the answer is (3x-2)(9x squared+6x+4)

This is impossible as the variables are different

It is: 2(3x-7y) = 6x-14y

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

3x squared - (3x) squared = 0